Regenerative Anthropology in Fact, Fiction, and Prophecy: Jefferson, Douglass, Twain, Lincoln - McKenna, Andrew J. (Anthropoetics, 2020)
This essay examines the explicit truth claims of certain canonical text of American literature, engaging the complementary insights of René Girard’s mimetic theory and Eric Gans’s generative anthropology as they apply to writings on slavery and the civil war that ensued over its continuation. Stylistic analysis is especially enabled by Gans’s attention to constative and performative aspects of human language, as cannily wielded by the authors studied here. The insights of Girard and Gans afford the opportunity to appraise the indissociable epistemic, esthetic and ethical valences of literary masterpieces.